Importance-performance matrix of analysis on factors influencing language ability among Malaysian higher learning ESL learners / Tg Nur Liyana Tengku Mohamed Fauzia, Muhammad Saiful Anuar Yusoff and Ahmad Mazli Muhammad - Tengku Mohamed Fauzia, Tg Nur Liyana; Yusoff, Muhammad Saiful Anuar; Muhammad, Ahmad Mazli (UiTM Press, 2022)
There has been extensive research in the field of second language acquisition resulting in the introduction of various methods to help individuals learn ESL. In Malaysia, for example, different methods to empower graduates with English language skills have been introduced and discussed. One of the issues addressed is related to the limited exposure to ESL due to the changes of the English language status in Malaysia during the pre and post-independence era. A theoretical framework developed emphasizes five factors in the learning process which include implicit and explicit exposure to ESL, the cognitive learning dimensions (CLDs) consisting of motivation and memory strategies as the mediating variables, and language ability as the outcome. The question on what factors should be given priority has been raised in this study to ensure the result on the language ability is optimal. 460 responses were collected from undergraduate students in different public and private higher learning educations in Malaysia. 445 were analyzed in PLS-SEM for structural model analysis. Hypotheses testing revealed that all four factors have a positive relationship, and the Importance-Performance Matrix Analysis (IPMA) shows that explicit exposure is the most important factor while motivation has the lowest importance. Memory strategies, among other variables, should be given the priority for further research due to its second highest importance in the framework but contributing the least to language ability performance. One of the reasons is due to the practice of rote memorization among Malaysian ESL learners which should be transformed into an effective memory strategy in ESL learning.